Pemaliq: Myth as an Effort to Defend the Customs of Sasak in Desa Beleq Hamlet, Gumantar, North Lombok - Adi Putro Aji Wicaksono; Okta Hadi Nurcahyono; Sigit Pranawa (Humanus, 2020)
The effect of modernization and globalization is, among other, the degraded ancestor custom and traditions. So many cultural strategies are taken by the community, particularly customary community to maintain custom and tradition. This research aims to find out why Desa Beleq Hamlet customary community still maintain Sasak tribal custom and tradition in Lombok Island through Adat Tau Lokaq Lima regulation. This study belongs to qualitative research with ethnographic approach aiming to give a holistic representation about the cultural event occurring. The author used in-depth interview and participatory observation in collecting data of research. The result of research showed that pemaliq, as a prohibition constructed in human reasoning on the event to befall an individual or a group of individuals violating the ancient myths told hereditarily, could create a community’s holistic understanding to comply with the existing custom.